The original political legitimacy of the Ethiopian ethnic federal system: from the perspective of multiparty deliberative constitution-making - Getahun, Yohannes Haile (Ethiopian Journal of Social Sciences, 2023)
This article deals with the political legitimacy of the ethnic federal system of Ethiopia in terms of multiparty federal constitutional designing. It applies the research design of a qualitative interpretive case study which uses theoretical perspectives and empirical data without undermining the contextual particularities of the case under investigation. Theoretical elaborations in conjunction with the annals of constitution-making across mature, fragile, and defunct multi-ethnic and multi-national federations are the literature review aspects of the article. They underline the conceptual and empirical frameworks of the study that multiparty constitution-making is of paramount significance to the foundational original legitimacy of federal systems. Based on that, the article has employed predominantly qualitative data, primary and secondary, and information from the literature and public and official documents related to the making of the Ethiopian Federal Constitution. It is found that the dominance of EPRDF (Ethiopian Peoples' Revolutionary Democracy) in the designing of the 1994 Federal Constitution was hardly aligned with multiparty federal constitutional designing. As a result, the ethnic federal system has been challenged for two reasons. First, it is a top-down and exclusive constitutional imposition by primarily EPRDF and its allies, which were less popular, newly organized, and urban-based minor ethnic parties. Relatively popular ethnic and cross-ethnic opposition parties did not take part in the writing ventures of the federal constitutional dispensation. The other reason is a substantive one that the Marxist-Leninist derivatives of EPRDF's revolutionary-democracy envisaged the relegation of, among others, the liberal values of individual rights and democratic citizenship into the ethnic structure of self-determination. That, exemplified by the defunct communist federations, raises questions about the ideological legitimacy of the EPRDF-backed federal order. As a remark, inclusive, open and genuine constitutional dialogues and bargains could redeem the contested origin of the ethnic federal system. That goes in tandem with the democratization process of Ethiopia, which is still controversial.